A cross‐sectional evaluation of the validity of a smartphone otoscopy device in screening for ear disease in Nepal. (28th May 2017) - Mandavia, R.; Lapa, T.; Smith, M.; Bhutta, M.F.
Abstract : Objectives: Hearing loss is a neglected international health problem. The greatest burden of ear disease is in low‐income countries where there is also a lack of resources. In this context, screening for otological disease may be worthwhile. Cupris© has developed an otoscopy device that offers the possibility of low‐cost mass screening in remote communities. We evaluated the validity of this device in diagnosing ear disease and in determining whether referral to an ENT centre is warranted. Design: Cross‐sectional study. Setting: Outpatient clinic, Nepal. Participants: All adults and children were invited to take part over a 2‐day period. The Cupris© device was used to record participants otological history and examination. Stored history and images were assessed in the United Kingdom by a Consultant‐grade ENT Surgeon, who provided a diagnosis and decided whether referral to an ENT centre was warranted. After screening with the Cupris© device, participants were immediately assessed by a UK trained ENT Consultant Surgeon using a standard otoscope ("standard assessment"). A diagnosis was recorded for each participant and a decision was made as to whether referral to an ENT centre was warranted. Outcomes: Concordance in primary diagnosis (analysed per ear) and concordance in the decision to refer (analysed per patient). Cohen's kappa coefficient for inter‐rater agreement in diagnosis. Results: Fifty‐six patients agreed to participate. In four patients, the quality of video recorded precluded a diagnosis or management plan. These patients were excluded from subsequent analysis, leaving 52 patients for analysis. The same diagnosis was reached for 99 of 104 ears when comparing the Cupris© device to standard assessment (95% concordance), with Cohen's kappa coefficient of 0.89. The decision as to whether a patient should be referred to an ENT centre for further assessment was the same for all 52 participants when comparing the Cupris© device to standard assessment. Conclusions: When compared to standard assessment, the Cupris© device is a valid tool for the diagnosis of ear disease and decision for onward referral. It shows considerable promise for use by trained non‐medical workers, as a low‐cost and portable tool to screen for ear disease in remote settings, particularly in low‐ and middle‐income countries.